China’s belt and road initiative (BRI) and the Duterte administration’s appeasement policy: Examining the connection between the two national strategies - De Castro, Renato Cruz (Animo Repository, 2019)
This article examines the link between the Belt and Road Initiative (BRI) and the Duterte Administration’s appeasement policy on China. Relative to the South China Sea dispute, China uses the BRI as a means to ease and stabilize its strained relations with claimant countries like the Philippines. The BRI has enabled China to influence the Philippines in changing its policy on Chinese maritime expansion in the South China Sea. Lured by the BRI, President Rodrigo Roa Duterte is undoing his predecessor’s policy of balancing China’s expansive claim in the disputed waters. Based on his calculation, the Philippines will benefit from the BRI initiative—particularly in the revival of the maritime silk route—as it dovetails with his administration’s massive infrastructure build-up program. In conclusion, the article contends that President Duterte is convinced that his appeasement policy toward China is worth pursuing because it makes the Philippines a beneficiary of the BRI. However, 3 years into his term, he has yet to see the implementation of BRI-funded infrastructure projects, which have been delayed by technical problems, the Philippine military, and the Filipino people’s distrust of China because of the South China Sea issue in particular, and its behavior as emergent power in East Asia in general. © 2019, Springer Nature B.V.